Variability in Epicuticular Wax in 35 Woody Plants in Linares, Northeast Mexico - Maiti, Ratikanta; Rodriguez Gonzalez, H.; Gonzalez, E. A.; Kumari, Aruna; Sarkar, N. C. (OMICS Publishing Group, 2016)
A study has been undertaken on epicuticular wax on the leaves of 35 woody species in Linares, Northeast Mexico at the experimental station of Facultad de Ciencias Forestales, Universidad Autonoma de Nuevo Leon, located in the municipality of Linares. Considerable variation in wax accumulation was found among species showing prominent interspecific variation. Wax load varied from 11.18 to 702.04 µg/cm2 among species studied during summer. Few species selected with high epicuticular wax viz, Forestiera angustifolia (702.04 µg/cm2), Diospyros texana (607.65 µg/cm2 ), Bernardia myricifolia (437.53 µg/cm2), Leucophylum leucocephala (388.50 µg/cm2), during summer which could well be adapted under semi-arid environments for their efficiency in the reflection of radiation load, reduced transpiration, gas exchange and probably impart drought resistance. The large variations in epicuticular wax could be related to their physiological functions such as transpiration, gas exchange, water relations etc.